Linear ordering of selected gerontechnologies using selected MCGDM methods - Halicka, Katarzyna; Kacprzak , Dariusz (Technological and Economic Development of Economy, 2021)
For over last 20 years, significant changes have been observed in the age structure of the world’s population. The percentage of working-age population is steadily decreasing all over the world, and a relative number of retired people is increasing. It confirms that our society is ageing. Moreover, according to the United Nations population forecast the situation will get worse. The increasing number of seniors is also connected with the need to provide them with institutional support in the form of care. One of the key elements of helping older adults may be gerontechnology – an interdisciplinary field of research that uses technology to implement the aspirations and abilities of seniors.On the basis of a meticulous literature review, 9 groups of gerontechnology have been identified that have been rated with respect to 30 criteria. In the period December 2019 – January 2020 a representative sample of 1.152 Poles aged over 40 (acting as decision makers) took part in the research consisting of completing the prepared questionnaire. Based on selected Multiple Criteria Group Decision Making methods, linear ordering of gerontechnologies was prepared and the most preferred by respondents participating in the study was indicated.